Effects of a structured, family-supported, and patient-centred advance care planning on end-of-life decision making among palliative care patients and their family members: protocol of a randomised controlled trial - Doris Y. P. Leung; Joyce O. K. Chung; Helen Y. L. Chan; Raymond S. K. Lo; Kevin Li; Po Tin Lam; Nancy H. Y. Ng (BMC Palliative Care, 2024)
Abstract Background Advance care planning (ACP) is a well-recognized quality indicator for palliative care. Despite two decades of effort, previous studies showed that ACP-related documentation and end-of-life discussion rates remain low for palliative care patients. Although ACP is about self-determination and autonomy, studies consistently show the importance of family involvement in adult patient’s medical decision-making. Yet, research on ACP interventions with structured components targeting family member remained limited. The current study aims to evaluate the effectiveness of a structured, family-supported, patient-centred ACP programme for adult palliative care patients and their families. Methods This is a 2-arm parallel group randomized controlled trial with follow-ups at 6 and 12 months. One hundred and seventy eligible palliative care patients and their families are planned to be recruited from three hospitals, and randomized to either a structured, family-supported, patient-centred ACP programme (ACP-Family) or usual ACP care (ACP-UC) arm. The ACP-Family intervention consists of 2 sessions. The primary outcome is family’s prediction accuracy of patient’s treatment preferences at 6 months. Secondary outcomes include proportions of new ACP documentations and family-reported perception of whether the patient’s end-of-life (EOL) care preference was respected; patient’s decisional conflict; quality of communication; family’s decision-making confidence; family’s anxiety and depression; and patients’ and family members’ satisfaction of the intervention. Outcomes of the two groups will be compared using regressions and linear mixed-effects models. Discussion This study will provide rigorous scientific evidence on the effectiveness of a structured and well-design family-supported, patient-centred ACP programme for adult palliative care patients and their family members in the hospital setting. If the ACP-Family proves to be effective, it will provide a structured and systematic approach to facilitate ACP discussions involving family members. This will respond to local needs and inform international ACP practice. Trial registration ClinicalTrials.gov Identifier: NCT05935540.